2022
DOI: 10.1002/cne.25401
|View full text |Cite
|
Sign up to set email alerts
|

The parabigeminal nucleus is a source of “retinogeniculate replacement terminals” in mice that lack retinofugal input

Abstract: In the dorsal lateral geniculate nucleus (LGN) of mice that lack retinal input, a population of large terminals supplants the synaptic arrangements normally made by the missing retinogeniculate terminals. To identify potential sources of these "retinogeniculate replacement terminals," we used mutant mice (math5 -/-) which lack retinofugal projections due to the failure of retinal ganglion cells to develop. In this line, we labeledLGN terminals that originate from the primary visual cortex (V1) or the parabigem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…While these interactions could be mediated by extrinsic sources (e.g. cortex, 39 ; thalamic reticular nucleus, 40,41 ; superior colliculus, 42 ; pretectum, 43,44 ; or parabigeminal nucleus, 29,45 ), our study indicates that geniculate interneurons provide one of the first locations where signals from the two eyes can be compared, integrated, and adjusted before being transmitted to cortex. Whether these interneuron-mediated binocular interactions translate to species where retinogeniculate inputs from the two eyes are more highly segregated and arranged in a laminar fashion, requires additional investigation.…”
Section: Functional Implicationsmentioning
confidence: 70%
See 1 more Smart Citation
“…While these interactions could be mediated by extrinsic sources (e.g. cortex, 39 ; thalamic reticular nucleus, 40,41 ; superior colliculus, 42 ; pretectum, 43,44 ; or parabigeminal nucleus, 29,45 ), our study indicates that geniculate interneurons provide one of the first locations where signals from the two eyes can be compared, integrated, and adjusted before being transmitted to cortex. Whether these interneuron-mediated binocular interactions translate to species where retinogeniculate inputs from the two eyes are more highly segregated and arranged in a laminar fashion, requires additional investigation.…”
Section: Functional Implicationsmentioning
confidence: 70%
“…The physiological responses recorded in our study corroborate the known anatomical connections within the dLGN. Whyland et al, 29 found no significant differences in the sizes of contralateral and ipsilateral retinogeniculate terminals in the mouse and no difference in the proportion of their synaptic contacts on interneurons (ipsilateral 12%, contralateral 13%) and relay cells (ipsilateral 88%, contralateral 87%). Thus, although ipsilateral and contralateral retinogeniculate terminals originate from different subsets of retinal ganglion cells 30 , they do not differentially innervate relay cells versus interneurons.…”
Section: Anatomical Connections Underlying the Observed Physiological...mentioning
confidence: 94%
“…This result is consistent with findings from the superior colliculus, where anterograde transport loss precedes synaptic loss ( Crish et al, 2010 ; Smith et al, 2016 ). However, some remaining vGlut2 signal might also originate from tectogeniculate synaptic inputs arising from vGlut2-expressing projection neurons in the stratum griseum superficiale of the superior colliculus ( Fremeau et al, 2001 ; Bickford et al, 2015 ) or potentially other “replacement terminals” ( Whyland et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…This mutant lacks the transcription factor Math5, which is essential for the differentiation of retinal progenitors into retinal ganglion cells. As a result, Math5 −/− mice exhibit a wholesale loss (> 95%) of retinal ganglion cells, a failure to develop an optic nerve, and a brain that is devoid of retinofugal projections [31][32][33][34]. Finally, because our focus is on visual intrathalamic circuits, we also assessed whether the modality-speci c sectors of TRN were present at birth and if such an arrangement was altered by visual deafferentation.…”
Section: Introductionmentioning
confidence: 99%